Independent and joint impacts of high body mass index and aging on global burden of chronic kidney disease: insights from the Global Burden of Disease Study 2021 - Ma, Yao; Chen, Shun; Shen, Yuanli; Wang, Xiang; Xie, Xinning; Zhao, Weihong (Frontiers in Nutrition, 2025)
IntroductionWe aimed to evaluate the levels and trends of CKD burden associated with high body mass index (BMI) from 1990 to 2021 and to investigate the role of aging.MethodsFrom the Global Burden of Disease Study 2021, we retrieved data and estimated CKD-related deaths, disability-adjusted life years (DALYs), age-standardized mortality rate (ASMR), and age-standardized DALYs rate (ASDR) attributable to high BMI by age, sex, socio-demographic index (SDI), and geographical regions. We calculated the estimated annual percentage changes (EAPCs) from 1990 to 2021 and projected attributable CKD burden through 2050. A cluster analysis was performed to identify changing patterns. We also used the decomposition analysis to evaluate the role of aging in observed trends.ResultsGlobally, high BMI was responsible for 418,402 CKD-related deaths and 1.04 million DALYs in 2021. The ASMR and ASDR were 5.06 and 122.08 per 100,000 population, showing an increasing trend from 1990 to 2021. The predicted results indicated that the attributable CKD burden will continue to rise through 2050. Males exhibited higher ASRs and EAPCs. Substantial geographic and regional disparities were observed, with an inverted “U”-shaped relationship between ASRs and SDI. With advancing age, the burden increased consistently, and sex differences varied. Decomposition analysis revealed that population aging was one contributing factor to the observed trends.ConclusionGlobal CKD burden attributable to high BMI remains substantial. These findings underscore the urgency to address the growing public health challenge posed by obesity. Given the age, sex, and geographic differences, targeted strategies are needed.